Avaliação quantitativa da susceptibilidade do crescimento de Staphylococcus aureus na presença de sistemas antimicrobianos de alta complexidade - Garrido, Saulo Santesso; de Oliveira, Isabelle Cavalini; Zambom, Carolina Reis; Vaz, Aline Buda dos Santos; Marchetto, Reinaldo; Barbosa, Luiz Carlos Bertucci (Eclética Química, 2016)
Antimicrobial peptides (PAMs) found naturally in living organisms are a great promise for the fight against infectious diseases specially by microorganisms multiresistant to the commercial antibiotics available on the market due to intensive and inadequate applying of those substances. However, some particular characteristics that may be present in PAMs (big size, low solubility, the existence of effective load, high structural complexity, etc.) pose difficulty vis-à-vis the use of this class of substances for clinical application. As an approach to solve this technical barrier to application of PAMs, different formulations of LUV liposomes were prepared with the intent to promote the encapsulation of CcdBET2, a proven PAM, and promote its delivery in the intracellular environment. CcdBET2 was synthesized by solid-phase methodology and the 100 nm liposomes by extrusion. The peptide-liposomes systems were tested against Staphylococcus aureus by a quantitative methodology using MTT to test their ability in promote the interruption of cell growth. It is possible to suggest that the liposomal system is responsible to interact with the bacterial membrane allowing CcdBET2 to exert its antimicrobial activity.